METHOD AND SYSTEM FOR COMPUTATIONAL DESIGN AND MODELING - BHAT, MANOJ; SHAH, SAPANKUMAR HITESHCHANDRA; GHAISAS, SMITA SUBHASH; KULKARNI, NAGESH HARI; KUMAR, PRABHASH; YEDDULA, RAGHAVENDRA REDDY; REDDY, SREEDHAR SANNAREDDY; SINGH, AMARENDRA KUMAR; BASAVARSU, PURUSHOTTHAM GAUTHAM; DAS, PRASENJIT (2014)
The present subject matter discloses a method and a system for computational design and modeling. The method includes, identifying, by a processor (202), requirements and desired properties of a product being developed based on a product development request. One or more processes and materials suitable for developing the product are determined using a materials ontology, a product and process ontology instance, material knowledge elements, and product and process knowledge elements based on the identification. Processing of the material is simulated for developing a simulated product using one or more simulation tools based on the determination. Further, the processor (202) ascertains whether the simulated product meets the requirements and the desired properties. Further, a knowledge base (108) having knowledge and ontology instances corresponding to the material, the process, and the simulation tool is updated based on the assertion for being used for design and modeling of the product and similar products. La présente invention porte sur un procédé et un système de conception et modélisation par ordinateur. Le procédé consiste à identifier, par un processeur (202), des exigences et des propriétés souhaitées d'un produit en train d'être développé sur la base d'une requête de développement de produit. Un ou plusieurs processus et un ou plusieurs matériaux appropriés pour développer le produit sont déterminés, à l'aide d'une ontologie de matériaux, d'une instance d'ontologie de produits et de processus, d'éléments de connaissances de matériaux et d'éléments de connaissances de produits et de processus, sur la base de l'identification. Un traitement du matériau est simulé pour développer un produit simulé à l'aide d'un ou plusieurs outils de simulation sur la base de la détermination. En outre, le processeur (202) évalue si le produit simulé répond ou non aux exigences et aux propriétés souhaitées. En outre, une base de connaissances (108) comprenant des instances de connaissances et d'ontologies correspondant au matériau, au processus et à l'outil de simulation est mise à jour sur la base de l'évaluation en vue d'être utilisée pour concevoir et modéliser le produit et des produits similaires.